High prevalence of Rickettsia spp. in ticks from wild hedgehogs rather than domestic bovine in Jiangsu province, Eastern China - Qi, Yong; Ai, Lele; Jiao, Jun; Wang, Junhu; Wu, Deping; Wang, Pengcheng; Zhang, Guoyu; Qin, Yong; Hu, Cheng; Lv, Ruichen; Lu, Nianhong; Zhu, Changqiang; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Spotted fever group Rickettsia (SFGR), containing various pathogenic Rickettsia spp., poses remarkable negative influences to public health by causing various severe or mild diseases. Information regarding prevalence of SFGR in ticks in Jiangsu province, Eastern China, is still limited and needs urgent investigations. Methods Hedgehog- and bovine-attached ticks were collected from Jiangsu province, Eastern China. DNA of individual ticks was extracted for nested polymerase chain reaction amplifications targeting gltA, 16S ribosomal RNA (rrs), ompA, ompB, and sca4 genes following with sequencing. SFGR-specific IgG antibodies in sera of local donators were evaluated using ELISA. Results Overall, 144 (83.2%) of the 173 ticks from hedgehogs and 2 (1.2%) of the 168 ticks from bovine were positive for one of the three identified Rickettsia spp., with significant difference between the two groups (P = 3.6e-52). Candidatus Rickettsia principis (9; 5.2%) and R. heilongjiangensis (135; 78.0%) were detected in Haemaphysalis flava rather than in H. longicornis ticks from hedgehogs. R. heilongjiangensis (1; 0.6%) and Candidatus R. jingxinensis (or Candidatus R. longicornii) (1; 0.6%) were identified in H. longicornis and Rhipicephalus microplus ticks from bovine, respectively. Phylogenetic analysis indicated Candidatus R. jingxinensis belonged to R. japonica subgroup, whereas Candidatus R. principis belonged to a novel subgroup. Higher serological prevalence of spotted fever and SFGR-specific IgG antibody level in humans were observed around the investigated area than in urban areas, without significant difference. Conclusion Candidatus R. principis and Candidatus R. jingxinensis were identified in Jiangsu province, Eastern China, and fully genetically characterized for the first time. The higher prevalence of SFGR in hedgehog-attached ticks as well as the higher SFGR-specific IgG antibody level and seropositive rate in humans around the investigated area suggested that more attention should be paid to SFGR. This pathogen is usually transmitted or harbored by wild animals and ticks. This study provides important epidemiological data for both physicians and public health officers in developing early prevention and control strategies against potential Rickettsia infections and in the preparation of suitable testing and treatment needs for rickettsiosis in the endemic areas.